Mechanisms of esophageal cancer metastasis and treatment progress - Wang, Yusheng; Yang, Wei; Wang, Qianyun; Zhou, Yong (Frontiers in Immunology, 2023)
Esophageal cancer is a prevalentcommon digestive tract tumor in the worldworldwide. The detection rate of early -stage esophageal cancer is very low, and most patients are found to have metastasis after diagnosis。. Metastasis of esophageal cancer mainly includes direct diffusion metastasis , hematogenous metastasis and lymphatic metastasis. This article summarizes reviews the metabolic process of esophageal cancer metastasis, the mechanism by which M2 macrophages, CAF, regulatory T cells and their released cytokines, including chemokines, interleukins, and growth factors, form an immune barrier to the anti-tumor immune response mediated by CD8+T cells and impede their killing of tumor cells during tumor immune escape. The effect of Ferroptosis on metastasis of esophageal cancer is briefly mentioned. also Moreover the paper also summarizes the common drugs and research directions in chemotherapy, immunotherapy and targeted therapy for advanced metastatic esophageal cancer.